Comparison of Added Value between Bioethanol Production and the Most Important Animal Production Branches Based on Concentrated Fodder, as Potential Competitors - Jobbágy, Péter (Acta Agraria Debreceniensis, 2010)
There are an enormous amount (2-3 million t/yr) of corn surplus is available year by year in Hungary. Inland utilization is an unsolved problem, whereas export facilities of raw (unprocessed) material could not be regarded as optimal way because of logistical barriers and the very low producer’s price. There are two basic opportunities for the export of the surplus of maize with reduced transportational costs and higher value: animal production and process of bio-ethanol. In Hungarian conditions both of them demand the same raw material so they should compete with each other for maize. Both need financial aid at least for the investment in order to reach profit. Decision makers are influenced by several factors in allocating of national supports between the differential branches, one of them could be the added value developing in the given vertical change. I will introduce and analyze the expectable added values of the abovementioned competitive activities.